Recovery of assets, the result of acts of public corruption, from the power of third parties: Reference to Paraguayan legislation and comparative law (Legal journal - Research in Legal and Social Sciences, 2017)
The concept of public corruption originated with the creation of the first forms of social organization: tribe, monarchy, empire, republic, state, etc. representing a problem that is difficult to solve due to the speed of its extension and the profound disintegration it causes in public institutions. In turn, the fight against corruption has evolved, consolidating its importance, but to fight against corruption, tools are needed that produce the desired result: recover the assets that have left the State illegitimately and not be limited to the imposition of sanctions. traditional penalties. Public corruption is not the exclusive responsibility of public officials, although they may be imputed to some degree of participation depending on the presuppositions of the punishable act in question, there are other non-punishable participants who intervene to make it possible to disguise goods resulting from acts of corruption, they are called third parties. Those third parties could be direct beneficiaries of the illicit assets or be proxies, and the existence of fraud is not necessary - knowing and wanting, - but guilt and error can coexist as elements present at the time of carrying out the legal act of disposition. . Faced with such a distinction, the figures of the third party of good and bad faith arise. – but that fault and error can coexist as elements present at the time of carrying out the legal act of disposition. Faced with such a distinction, the figures of the third party of good and bad faith arise. – but that fault and error can coexist as elements present at the time of carrying out the legal act of disposition. Faced with such a distinction, the figures of the third party of good and bad faith arise.
Keywords: comparative law; power of third parties; acts of public corruption; Asset recovery